Predictive clinical parameters for the response of nivolumab in pretreated advanced non-small-cell lung cancer - Yuko Oya; Tatsuya Yoshida; Hiroaki Kuroda; Masashi Mikubo; Chiaki Kondo; Junichi Shimizu; Yoshitsugu Horio; Yukinori Sakao; Toyoaki Hida; Yasushi Yatabe (2017)
Nivolumab offers a superior survival benefit over docetaxel in patients with advanced, previously treated non-small-cell lung cancer (NSCLC). An association between programmed cell death ligand-1 (PD-L1) expression and the efficacy of nivolumab has been reported in many studies. However, the association between the clinical parameters and efficacy of nivolumab remains unclear in advanced NSCLC patients.Among 124 patients, 108 (88%) were performance status (PS) 0 to 1. PD-L1 expression was assessed in 89 patients, with 51 (57%) patients having PD-L1 positive expression. In all patients, the objective response rate (ORR) in patients with elevated CRP levels (≥ 1 mg/dl) was significantly worse than those without elevated CRP levels (< 1 mg/dl) (8.3 vs 23.4%, p = 0.0180). The PS (≥ 2), smoking index (< 400), CRP levels (≥ 1 mg/dl) and LDH (≥ 245 IU/L) were significantly associated with a shorter PFS and OS in patients treated with nivolumab. Multivariate analyses showed that the PS (≥ 2), smoking index (< 400), CRP levels (≥ 1 mg/dl) and LDH (≥ 245 IU/L) and PD-L1 expression were significant factors associated with a longer PFS of nivolumab.We retrospectively analyzed 124 patients who received nivolumab as a subsequent treatment. The patient characteristics, laboratory data at baseline (C-reactive protein [CRP] and lactate dehydrogenase [LDH]), PD-L1 expression, nivolumab response, progression-free survival (PFS), and overall survival (OS) were evaluated.Clinical parameters, such as PS, serum CRP, serum LDH, and smoking status, were significantly associated with the response duration and survival in patients treated with nivolumab.